2019
DOI: 10.1002/ar.24253
|View full text |Cite
|
Sign up to set email alerts
|

The Claustrum in the Squirrel Monkey

Abstract: The claustrum (CLA) is a subcortical structure that is reciprocally and topographically connected with the cerebral cortex. The complexity of the cerebral cortex varies dramatically across mammals, raising the question of whether there might also be differences in CLA organization, circuitry, and function. Species variations in the shape of the CLA are well documented. Studies in multiple species have identified subsets of neurochemically distinct interneurons; some data suggest species variations in the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 110 publications
0
10
0
Order By: Relevance
“…Macaques show a single class of large cells, some of which resemble cortical pyramidal neurons, others inhibitory interneurons (Reynhout & Baizer 1999). PV-positive neurons have also been reported in squirrel monkeys (Baizer et al 2020) and in marmosets (Pham et al 2019), the latter finding variable densities along the insular claustrum and the Endopiriform nucleus.…”
Section: Parvalbumin (Pv)mentioning
confidence: 87%
See 2 more Smart Citations
“…Macaques show a single class of large cells, some of which resemble cortical pyramidal neurons, others inhibitory interneurons (Reynhout & Baizer 1999). PV-positive neurons have also been reported in squirrel monkeys (Baizer et al 2020) and in marmosets (Pham et al 2019), the latter finding variable densities along the insular claustrum and the Endopiriform nucleus.…”
Section: Parvalbumin (Pv)mentioning
confidence: 87%
“…In the marmoset, the distribution of CB-positive neurons is heterogenous, with a high density of CBpositive neurons reported in the caudal sections of the Endopiriform nucleus (Pham et al 2019). In the squirrel monkey, CB immunoreactivity was only apparent in the somas and extreme proximal processes of positive neurons (Baizer et al 2020).…”
Section: Calbindin (Cb)mentioning
confidence: 99%
See 1 more Smart Citation
“…CBPs immunoreactivity was seen throughout the Cl of other mammal species (rat: Druga et al ., 1993; monkey: Reynhout and Baizer, 1999; cat: Hinova‐Palova et al ., 2007; Rahman and Baizer, 2007; human: Hinova‐Palova et al ., 2014; human, chimpanzee, macaque: Pirone et al ., 2014; dog: Pirone et al ., 2015; squirrel monkey: Baizer et al ., 2020), suggesting that similar subclasses of Cl neurons exist in multiple species and share a homogeneous spatial distribution pattern throughout the anterior–posterior extent of the Cl.…”
Section: Discussionmentioning
confidence: 99%
“…More than a decade ago, Crick and Koch (1) suggested that the claustrum plays a role in consciousness. Their integrated conscious percept model was based on the claustrum's widespread connectivity profile, with identified projections to and from the sensory, motor, and associative cortical areas (2)(3)(4)(5)(6)(7). Knowledge of the physiological functions of the claustrum evolved in the past few decades as advanced anatomic and electrophysiological approaches were applied to claustrum studies in various species (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%